Nonlinear observer-based control with application to an anaerobic digestion process. (January 2019) - Draa, Khadidja Chaib; Zemouche, Ali; Alma, Marouane; Voos, Holger; Darouach, Mohamed
Abstract: This paper deals with the design of a new observer based control strategy for an Anaerobic Digestion (AD) process to track a desired reference trajectory. The target is to control the biogas production, and to subsequently integrate the biogas plants in a virtual power plant. The used model is a two-steps (acidogenesis-methanogenesis) mass balance nonlinear, which is a widely used AD process model. Since the AD processes experience a lack of physical sensors, an exponential nonlinear observer is designed to estimate and update the internal state of the process. Based on the estimated states, a state feedback controller is used to track any given and admissible desired trajectory with respect to an H ∞ -optimality criterion. The observer-based controller parameters are designed by solving two (implicitly)-independent LMI conditions obtained by rigorous mathematical arguments based on a judicious use of Young relation and a reformulation of the Lipschitz property. A simulation study is provided to illustrate the validity and effectiveness of the proposed theoretical results.